KAJIAN KUALITAS AIR PERMUKAAN AKIBAT LIMBAH DOMESTIK DI HUTAN DESA BUMI LESTARI KABUPATEN KAPUAS HULU - Ramadhani, Endi; Lestariningsih, Siti Puji (Universitas Tanjungpura, 2024)
The use of surface water in the forest area of Bumi Lestari village for various needs is very intensive. On the other hand, there is no waste disposal system in the area, so waste from domestic activities is simply dumped directly into the water. The objectives of the study were to determine the distribution of water quality, the process of water self-purification, and to analyze the compliance of water quality with water quality regulation standards. Field survey methods and laboratory tests were used to determine water quality. Six test parameters were used, including TDS, TSS, BOD, COD, ammonia, and sulfate. The analysis of water quality compliance with water quality standards refers to the Government Regulation No. 22 of 2021. Water sampling was carried out using purposive sampling based on the condition of water flow and the segment of the settlement area, namely before (point 1), in the middle (point 2) and after (point 3). The results showed that the distribution of water quality in the rivers and lakes of the study area fluctuated. The increase of the degree of waste pollution was dominant at point 1, decreased at point 2, and increased again at point 3. The water self-purification process, based on to the BOD and COD indicators, can essentially take place, although pollutant levels increased again at point 3. Therefore, the final stage of the self-purification process has not yet been reached from the perspective of the water self-purification process zone. Based on Government Regulation No. 22 of 2021, the condition of the surface water quality in the study area, for the six parameters tested, shows that two parameters (BOD and ammonia) are classified in quality standard class IV, COD levels fall within quality standard classes I - II, and TDS, TSS, and sulfate levels are fall within quality standard class I.Keywords: Domestic Waste, Surface Water, Village Forest, Water QualityAbstrakPemanfaatan air permukaan di Kawasan Hutan Desa Bumi Lestari untuk berbagai kebutuhan begitu intensif dilakukan. Di sisi lain, pada kawasan tersebut belum terdapat sistem pengaturan pembuangan limbah, sehingga zat sisa hasil kegiatan domestik, dialirkan begitu saja secara langsung pada perairan. Tujuan dari penelitian diantaranya mengidentifikasi distribusi kualitas air, proses penjernihan kembali perairan, serta menganalisis kesesuaian kualitas air terhadap standar baku mutu air. Metode survei lapangan dan uji laboratorium digunakan untuk mengidentifikasi kualitas air. Enam parameter uji digunakan, diantaranya TDS, TSS, BOD, COD, Ammonia, dan Sulfat. Analisis kesesuaian kualitas air terhadap standar baku mutu air mengacu pada Peraturan Pemerintah (PP) Nomor 22 Tahun 2021. Pengambilan sampel air dilakukan secara purposif, berdasarkan kondisi pengaliran air dan segmen area permukiman, yakni sebelum (titik 1), tengah (titik 2), dan sesudah (titik 3). Hasil penelitian menunjukkan distribusi kualitas air pada perairan sungai dan danau daerah penelitian, memiliki kecenderungan pola yang fluktuatif. Peningkatan derajat pengotoran limbah yang dominan terjadi pada titik 1, penurunan pada titik 2, dan peningkatan kembali di titik 3. Proses penjernihan kembali menurut indikator BOD dan COD, pada dasarnya dapat terjadi, walaupun di titik 3 mengalami peningkatan kembali kadar pencemar, sehingga bila dilihat berdasarkan zona prosesnya, belum mencapai fase akhir dari proses penjernihan kembali. Berdasarkan PP No. 22 Tahun 2021, kondisi kualitas air permukaan daerah penelitian dari enam parameter yang diuji, dua parameter (BOD dan Ammonia) tergolong pada kelas baku mutu IV, kadar COD termasuk dalam kelas baku mutu I